“Internationalization at Home” in the United States: Enhancing admissions and enrollment practices for marginalized students during and after the COVID-19 pandemic (Comparative & International Education Series, 2021)
The COVID-19 pandemic has had a disproportionately negative impact on Black, Brown, Indigenous and low-income communities, further marginalizing already marginalized students and their families. The marginalization has placed these students at a greater disadvantage when applying to college, unless admissions and enrollment practitioners account for these disadvantages in their practices. In this chapter, we discuss college admissions and enrollment issues that directly impact marginalized students, including students of color and students from low-income households, and how the concept of “Internationalization at Home” could be used to build inclusive practices in admissions and enrollment during and after the pandemic. In doing so, we provide examples to illustrate how admissions and enrollment officers can incorporate the concept into their practice.How to cite this chapter:Muñiz, R., & Borg, N. (2022). “Internationalization at home” in the United States: Enhancing admissions and enrollment practices for marginalized students during and after the COVID-19 pandemic. In  R. Ammigan, R. Y. Chan, & K. Bista, (eds), COVID-19 and higher education in the global context: Exploring contemporary issues and challenges (pp. 38-50). STAR Scholars. https://starscholars.org/product/covid-19-and-higed/